Exploring Cannabidiol (CBD) and Cannabigerol (CBG) Safety Profile and Skincare Potential - Luz-Veiga, M; Mendes, A; Tavares-Valente, D; Amorim, M; Conde, A; Pintado, ME; Moreira, HR; Azevedo-Silva, J; Fernandes, J (My University, 2024)
Cannabinoids have long been known for their bioactive properties, with their topical application as anti-inflammatory compounds being at the forefront of research for the past decade. Concurrently, the cosmetic market is a fast-growing industry in constant need of new biomolecules. In this work, we studied the safety profile for topical applications of two cannabinoids: cannabidiol (CBD) and cannabigerol (CBG) and assessed their potential as skin care ingredients. The CBG used in this work resulted from bio-fermentation, and to the best of our knowledge, there are no extensive reports on its safety and usage as a cosmetic ingredient. Our results show that CBD and CBG do not exhibit cytotoxicity, mutagenicity, or skin sensitization. Moreover, we verified an absence of primary irritability, accumulated irritability, phototoxicity and photosensitization, supporting the claims of dermatologically tested, hypoallergenic and non-irritating. While these cannabinoids did not show significant anti-aging effects by altering the extracellular matrix components (both in vitro and ex vivo), they demonstrated promise as protective agents against inflammation caused by air pollution. Specifically, they reduced the levels of pro-inflammatory cytokines, making them valuable in combating environmental skin damage. Overall, our results validate the safety of topical use of cannabinoids, while paving the way for further research in the beauty and personal care market as soothing agents.
Keywords: Canabidiol; Canabinoids; Cuidados da Pele; Cannabidiol; Cannabinoids; Skin Care